Customer Satisfaction Index of Singapore: First Three Quarters Executive Summary 2009 - Institute of Service Excellence, SMU (Institutional Knowledge at Singapore Management University, 2009)
The Customer Satisfaction Index of Singapore (CSISG) is now in its third year, the results of the first three quarters of CSIS G 2009 were obtained from survey data gathered between April and August 2009. The six sectors measured were: Retail, Food and beverage, Info-communications, Education, Transportation and logistics, Tourism, hotels and accommodation services.